2006
DOI: 10.1002/lapl.200610098
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence monitoring with Doppler Optical Coherence Tomography

Abstract: The study of flow dynamics in micro vessels is highly important in rheology and cardiology to enable a better understanding of the effect of blood flow on the possible rupture of atherosclerotic plaques. Doppler Optical Coherence Tomography is able to provide a very high velocity resolution down to 10 μm s-1. The technique offers the potential to achieve a more detailed analysis of the flow/vessel interactions than current clinical practice offers; allowing simultaneously high resolution imaging of the morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 7 publications
(16 reference statements)
1
16
0
Order By: Relevance
“…Potential applications in blood monitoring also include measuring hemoglobin 7 and glucose 8 concentrations. The microflows have been extensively studied in complex vessels by Doppler OCT. [9][10][11][12][13] The spatial distribution of RBCs in microchannels has been previously evaluated with OCT. 14,15 Due to an insufficient axial resolution of the used OCT systems, the thickness of a CFL has not been measured previously.…”
Section: Introductionmentioning
confidence: 99%
“…Potential applications in blood monitoring also include measuring hemoglobin 7 and glucose 8 concentrations. The microflows have been extensively studied in complex vessels by Doppler OCT. [9][10][11][12][13] The spatial distribution of RBCs in microchannels has been previously evaluated with OCT. 14,15 Due to an insufficient axial resolution of the used OCT systems, the thickness of a CFL has not been measured previously.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its current limitations, a few studies can be found where DOCT has been applied for turbulent flow analysis-mainly for obtaining temporally averaged profiles. Bonesi et al (2007) used DOCT for monitoring turbulent velocity profiles in micro-channels. They observed, e.g.…”
Section: Turbulent Flowsmentioning
confidence: 99%
“…A number of new exciting applications have been developed in biomedicine, e.g. for cancer detection and treatment [17], for blood samples analysis [18], for monitoring efficiency of laser treatment of port-wine stains [19]; in physiological studies to monitor blood-oxygen saturation [20]; in cardiovascular applications [21]; in cell biology [22]; in vascular biology for monitoring blood and lymph microflows [23]; in tissue engineering for imaging of scaffold structure [24] and studying flows in artificial vessels [25,26]; in art conservation and archaeology [27], in the food industry for screening internal defects in fresh agricultural products [28], in developmental biology for cardiovascular deceases and heart-development studies [29], and others.…”
Section: Biophotonicsmentioning
confidence: 99%